2020
DOI: 10.1002/cbin.11363
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of epithelial–mesenchymal transition via sonic hedgehog/glioma‐associated oncogene homolog 1 signaling pathway in peritoneal mesothelial cells

Abstract: Sonic hedgehog (Shh) signaling regulating epithelial–mesenchymal transition (EMT) in cultured rat peritoneal mesothelial cells (PMCs) remains an under‐investigated topic. The current study aimed to elucidate the role of Shh signaling in the regulation of EMT in PMCs to attenuate peritoneal injury, with the view of enhancing the efficacy of peritoneal dialysis (PD). PMCs were initially extracted from male Wistar rats using pancreatic enzyme digestion. The expression of Shh and glioma‐associated oncogene homolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Consistently, the inhibition of Shh signaling by CPN could selectively block the proliferation of fibroblasts ( Figure 6 ). Zhou et al ( 39 , 42 ) showed that in different types of CKD, Shh specifically upregulated in renal tubular epithelial cells. It activated mesenchymal fibroblasts and promoted their proliferation through various mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, the inhibition of Shh signaling by CPN could selectively block the proliferation of fibroblasts ( Figure 6 ). Zhou et al ( 39 , 42 ) showed that in different types of CKD, Shh specifically upregulated in renal tubular epithelial cells. It activated mesenchymal fibroblasts and promoted their proliferation through various mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Shh also promoted the expression of FN and Vimentin and mediated the deposition of ECM ( 39 ). In ischaemia reperfusion injury (IRI) mouse model ( 39 , 42 ), overexpression of Shh promoted the proliferation of fibroblasts and ECM overproduction and deposition, eventually leading to kidney fibrosis and aggravated kidney function damage. Fabian et al demonstrated that recombinant Shh protein activated Ptch1/Gli1 signaling pathways in fibroblasts and induced the expression of α-smooth muscle actin (α-SMA), FN, and type I collagen, suggesting that Shh signal transduction activated fibroblasts to synthesize ECM ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…The experiments prove that BMSCs can reduce the AKI degree. However, some articles mentioned significant increase of Gli1+ MSCs in the medulla, cortex and around the entire renal artery in AKI caused by DDP and tamoxifen, most Gli1+ cells up-regulated the expression of α-SMA and GLI1+ BMSC accumulate around blood vessels after injury, which increased the risk of fibrosis [ 11 , 12 ]. Moreover, in the study of using BMSCs to treat pulmonary fibrosis, it was also found that the degree of pulmonary fibrosis can be inhibited by reducing Gli1.…”
Section: Discussionmentioning
confidence: 99%
“…According to research findings, when BMSCs were used to treat mice with AKI, the number of Gli1 + MSCs significantly increased in the renal medulla, renal cortex and around the entire renal artery. Moreover, the Gli1 + cells can up-regulate the expression of a-SMA and promote fibrosis development, i.e., there is the risk of promoting fibrosis during treatment of AKI using BMSCs [ 11 , 12 ]. However, there are no studies on how Gli1 regulates BMSCs to promote fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…The Hedgehog (Hh) signalling pathway is involved in cell cycle regulation and proliferation, cell adhesion and survival, EMT, self-renewal, and angiogenesis. 14 , 15 Many clinical studies have confirmed that Hh signalling is abnormally activated in lung adenocarcinoma, breast cancer, liver cancer, and other tumours, and is closely related to tumour development, prognosis, and drug resistance. 16 - 19 Hedgehog protein homologues, including sonic hedgehog (SHH), desert hedgehog (DHH), and Indian hedgehog (IHH), are highly expressed in the gastrointestinal tract, and the SHH protein is increased in gastric lesions and gastric cancer.…”
Section: Introductionmentioning
confidence: 99%